Analisis Penyebab Terjadinya Downtime di Pendaftaran Pada Aplikasi EPUS UPT Puskesmas Lubuk Baja - Situmorang, Masriani; Mulyana, Mulyana; Safitri, Risda (Transpublika Publisher, 2025)
The purpose of this study was to analyze the causes of downtime in the EPUS application used in the patient registration process. Downtime that occurs has an impact on delayed services, increased patient waiting time, and decreased efficiency and effectiveness of health services. The methods used in this activity are direct observation and interviews with registration officers. The results of the observation showed that downtime was caused by two main factors, namely internal network disruptions when inputting patient data and external server constraints when verifying BPJS active status. To overcome this problem, several short-term and long-term solutions were proposed, such as improving network infrastructure, training staff in manual procedures during downtime, and coordinating with BPJS. By implementing these solutions, it is hoped that services at the Puskesmas can remain optimal even though there are system disruptions.